The effect of steamed potato-wheat bread intake on weight, lipids, glucose, and urinary Na+/K+: A randomized controlled trial in Chinese adults - Xu, Haiquan; Guo, Yanzhi; Cai, Shaolun; Wang, Xiuli; Qu, Junling; Ma, Yunqian; Fang, Hongyun; Sun, Junmao (Frontiers in Nutrition, 2022)
Steamed potato bread has received much attention from nutritionists and agriculturalists since it became a staple food of China in 2015. Epidemiological studies have indicated that potatoes may cause diabetes and hypertension, but few trials have evaluated this effect. Through a clinical trial, we evaluated the effect of steamed potato bread intake on adults. In total, 49 and 30 individuals were assigned to the intervention and control groups, respectively. Steamed wheat bread (100% raw wheat flour) and potato-wheat bread (raw wheat flour and cooked potato flour in the ratio 3:7) were provided to the control and intervention groups, respectively, once a day for 4 weeks. Compared with the control group, the intervention group showed significant net changes in weight (−0.8 kg; 95% confidence interval [CI]: −1.4, −0.3; p = 0.005), body mass index (BMI, −0.3 kg/m2; 95% CI: −0.5, −0.1; p = 0.007), low-density lipoprotein cholesterol (LDL-c, −0.26 mmol/L; 95% CI: −0.49, −0.03; p = 0.025), and the urinary level of Na+/K+ (−2.3; 95% CI: −3.9, −0.7; p = 0.005). In conclusion, steamed potato-wheat bread intake for 4 weeks resulted in decreases in weight, BMI, LDL-c, and the urinary Na+/K+ level among Chinese adults